2022
DOI: 10.1103/physrevlett.128.221101
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Tidal Disruption Event AT2019fdr Coincident with a High-Energy Neutrino

Abstract: The origins of the high-energy cosmic neutrino flux remain largely unknown. Recently, one high-energy neutrino was associated with a tidal disruption event (TDE). Here we present AT2019fdr, an exceptionally luminous TDE candidate, coincident with another high-energy neutrino. Our observations, including a bright dust echo and soft late-time x-ray emission, further support a TDE origin of this flare. The probability of finding two such bright events by chance is just 0.034%. We evaluate several models for neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 133 publications
4
55
0
Order By: Relevance
“…TDEs have been suggested as candidates for producing highenergy protons and neutrinos (Murase et al 2020b), which is also supported by recently reported neutrino events associated with TDEs (e.g., Reusch et al 2022;Stein et al 2021;van Velzen et al 2021). However, with a steep spectrum of highenergy protons, it would be difficult for TDE outflows to account for the observed PeV neutrinos (Wu et al 2022).…”
Section: Discussionsupporting
confidence: 56%
“…TDEs have been suggested as candidates for producing highenergy protons and neutrinos (Murase et al 2020b), which is also supported by recently reported neutrino events associated with TDEs (e.g., Reusch et al 2022;Stein et al 2021;van Velzen et al 2021). However, with a steep spectrum of highenergy protons, it would be difficult for TDE outflows to account for the observed PeV neutrinos (Wu et al 2022).…”
Section: Discussionsupporting
confidence: 56%
“…We speculate that these could arise from jets or winds from the inner accretion disk that suddenly become more powerful as the SMBH accretion rate rises rapidly near the termination of the envelope cooling −contraction phase. Shocks driven by such outflows into the surrounding wind/envelope material could in principle accelerate relativistic ions, generating a source of high-energy gamma-rays and neutrinos (Lunardini & Winter 2017;Senno et al 2017;Guépin et al 2018;Fang et al 2020;Murase et al 2020), perhaps explaining the significant observed delay between the high-energy neutrino detections from a growing sample of TDE and the optical light-curve maximum (van Velzen et al 2021b;Stein et al 2021;Reusch et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several TDEs exhibit late-time radio flares, indicating mildly relativistic material ejected from the vicinity of the SMBH, but delayed from the optical peak by several months to years (e.g., Horesh et al 2021aHoresh et al , 2021bCendes et al 2022;Sfaradi et al 2022). A potentially related occurrence is the coincident detection of high-energy neutrinos from three optical TDEs by IceCube (van Velzen et al 2021b;Stein et al 2021;Reusch et al 2022), each of which also arrived several months after the optical peak. State transitions in the accretion flow offer one potential explanation for the delayed onset of jetted accretion activity (e.g., Tchekhovskoy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first detection of highenergy neutrinos of astrophysical origin by the IceCube Neutrino Observatory, the follow-up searches are ongoing to pinpoint the electromagnetic counterparts associated to the IceCube neutrino events (Abbasi et al 2021a;Garrappa et al 2019;Acciari et al 2021;Necker et al 2022;Stein et al 2022). A dozen of the neutrino events have been associated in likely coincidence with blazars, tidal disruption events, or superluminous SNe (Aartsen et al 2018a;Giommi et al 2020;Franckowiak et al 2020;Garrappa et al 2019;Krauß et al 2018;Kadler et al 2016;Stein et al 2021;Reusch et al 2022;Pitik et al 2022). As for LFBOTs, the IceCube Neutrino Observatory reported the detection of two track-like muon neutrino events in spatial coincidence with AT2018cow in the 3.5 days following the optical detection.…”
Section: Introductionmentioning
confidence: 99%